2005
DOI: 10.1063/1.2138804
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-doped zinc oxide tetratubes and their photoluminescent properties

Abstract: Manganese-doped zinc oxide tetratubes and their photoluminescent properties

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 44 publications
(52 reference statements)
2
9
1
Order By: Relevance
“…The polar E 1L mode is observed when the incident light is perpendicular to the c axis and A 1L mode is observed when the incident light is parallel to the c axis of ZnO [25,26]. Normally the E 1L mode is attributed to the oxygen deficiency and the A 1L mode is for the intrinsic defect in the sample such as oxygen vacancy and interstitial zinc [27][28][29]. Thus observed vibration frequencies corresponding to those modes clearly conforms the presence of the defects or vacancies.…”
Section: Article In Presssupporting
confidence: 75%
“…The polar E 1L mode is observed when the incident light is perpendicular to the c axis and A 1L mode is observed when the incident light is parallel to the c axis of ZnO [25,26]. Normally the E 1L mode is attributed to the oxygen deficiency and the A 1L mode is for the intrinsic defect in the sample such as oxygen vacancy and interstitial zinc [27][28][29]. Thus observed vibration frequencies corresponding to those modes clearly conforms the presence of the defects or vacancies.…”
Section: Article In Presssupporting
confidence: 75%
“…Disappearance of the Raman peak at ∼577 cm −1 in the annealed films, arising due to the Zn interstitials, may be related to the substitution of Mn 2+ in the Zn 2+ site with annealing. Xu et al [29] and Kim and Stair [30] observed the existence of a weak peak at about 665 cm −1 which was ascribed to the vibration mode of Mn-O. In the present study, the observed vibrational mode at ∼660 cm −1 in Mn:ZnO nanorod samples appeared only for samples containing higher amount of Mn.…”
Section: Raman Analysismentioning
confidence: 47%
“…Thus, we apprehend that this Raman peak at ∼660 cm −1 did not originate from possible partial formation of Mnrich solid solution layer in the Mn:ZnO nanorods or precipitation of ZnMn 2 O 4 . Rather, this peak might have originated from the combined effect of two-phonon signal of ZnO as indicated by Calleja and Cardona [32] and Hasuike et al [33] and the vibration mode of Mn-O as observed by Xu et al [29].…”
Section: Raman Analysismentioning
confidence: 86%
“…The other two peaks should be attributed to the 4 E(G) → 6 A 1 (S) and 4 T 2 (G) → 6 A 1 (S) transitions of Mn 2+ ions [8]. This behavior indicates that the Mn atoms have been doped into some lattice sites of ZnO [9].…”
Section: Resultsmentioning
confidence: 89%